2013
DOI: 10.1002/2013ja018833
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term modulations of Saturn's auroral radio emissions by the solar wind and seasonal variations controlled by the solar ultraviolet flux

Abstract: [1] Saturn's auroral activities have been suggested to be controlled by the seasonal variations of the polar ionospheric conductivities and atmospheric conditions associated with the solar extreme ultraviolet (EUV) flux. However, they have not yet been explained self-consistently by only the seasonal solar EUV effects. This study investigates the long-term variations of Saturnian Kilometric Radiation (SKR) as a proxy of the auroral activities, which were observed by Cassini's Radio and Plasma Wave Science expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 57 publications
(87 reference statements)
2
41
0
Order By: Relevance
“…It is undoubtedly true that Saturn's magnetospheric dynamics is influenced by several different drivers. Kimura et al [2013] suggested that at Saturn solar wind variations on solar cycle timescale affect the long-term magnetosphere-ionosphere coupling process on top of the baseline of the seasonal variations. This would seem to agree with the results presented here where we have observed a seasonal cause of the north-south asymmetry in the PPO periods seemingly associated with solar illumination and the abrupt changes in PPO behavior associated solar wind compressions and expansions.…”
Section: 1002/2015ja021642mentioning
confidence: 99%
See 1 more Smart Citation
“…It is undoubtedly true that Saturn's magnetospheric dynamics is influenced by several different drivers. Kimura et al [2013] suggested that at Saturn solar wind variations on solar cycle timescale affect the long-term magnetosphere-ionosphere coupling process on top of the baseline of the seasonal variations. This would seem to agree with the results presented here where we have observed a seasonal cause of the north-south asymmetry in the PPO periods seemingly associated with solar illumination and the abrupt changes in PPO behavior associated solar wind compressions and expansions.…”
Section: 1002/2015ja021642mentioning
confidence: 99%
“…They also reported that the pulsing of the SKR during these disturbed intervals was not significantly altered relative to that during nondisturbed intervals. Kimura et al [2013] presented a long-term correlation analysis between SKR, solar EUV flux, and propagated solar wind parameters, where they focused on variations with timescales in excess of several weeks. The study was performed during southern hemisphere summer from 2004 to 2010 during the declining phase of the solar cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The SKR energy flux and spectral range depend on the spacecraft location, because of the non-uniform spatial distribution of SKR sources and and the hollow cone emission pattern [Lamy et al, 2008;Kimura et al, 2013]. SKR emissions are usually not observed in the equatorial shadow zone (ESZ), which extends in radial distance from Saturn out to 4-7 R S , depending on frequency [Lamy et al, 2008].…”
Section: Data Selection Criteriamentioning
confidence: 99%
“…SKR emissions are usually not observed in the equatorial shadow zone (ESZ), which extends in radial distance from Saturn out to 4-7 R S , depending on frequency [Lamy et al, 2008]. The N-and S-SKR are mainly observed in the latitude of −20 -+70 deg and −60 -+10 deg, respectively [Kimura et al, 2013]. In observer's local time (LT), SKR is stronger in the dawn side sector, ∼2-10 h LT.…”
Section: Data Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation